Dual investigation of methanogenic processes by quantitative PCR and quantitative microscopic fingerprinting. Issue 1 (15th September 2014) - Kim, Yong Sung; Westerholm, Maria; Scherer, Paul
Abstract Monitoring of methanogenic communities in anaerobic digesters using molecular‐based methods is very attractive but can be cost‐intensive. A new and fast quantification method by microscopic image analysis was developed to accompany molecular‐based methods. This digitalized method, called quantitative microscopic fingerprinting (QMF), enables quantification of active methanogenic cells (N mL−1) by their characteristic auto‐fluorescence based on coenzyme F420. QMF was applied to analyze the methanogenic communities in three biogas plant samples, and the results were compared with the relative proportion of gene copy numbers obtained with the quantitative PCR (qPCR). Analysis of QMF demonstrated dominance of Methanomicrobiales and Methanobacteriales in relation to the total methanogenic community in digesters operating at high ammonia concentrations, which corresponded to the results established by qPCR. Absolute microbial counts by QMF and the numbers obtained by qPCR were not always comparable. On the other hand, the restricted morphological analysis by QMF was enhanced by the capability of qPCR to identify microbes. Consequently, dual investigations of both methods are proposed to improve monitoring of anaerobic digesters. For a rough estimation of the methanogenic composition in anaerobic digesters, the QMF method seems to be a promising approach for the rapid detection of microbial changes.